Seaweed extract of Gracilaria verrucosa as an antibacterial and treatment against Vibrio harveyi infection of Litopenaeus vannamei - Mad Rudi; Sukenda Sukenda; Dinamella Wahjuningrum; Wesly Pasaribu; Dendi Hidayatullah (Jurnal Akuakultur Indonesia)
ABSTRACT The objectives of this study were to investigate the antibacterial activity of G. verrucosa extract in test inhibitory zone with different concentrations (500, 1000, 1500, and 2000 mg/L) and  to examine G. verrucosa extract with different dosage (0.5, 1.0, 1.5, 2.0 g/kg) in feed on immune responses (total hemocytes count, phagocytic activity, phenoloxidase activity, respiratory burst) and survival rate in the Litopenaeus vannamei against the pathogenic Vibrio harveyi. Pacific white shrimp with an initial body weight of 5.25±0.55 g was reared in the aquarium (60×30×30 cm3) with a density of 10 shrimp/aquarium. Pacific white shrimp had been fed three times a day as much as 3% in at satiation for 14 days after challenged with V. harveyi. The first results of the inhibitory test showed that all the concentration of G. verrucosa extract was able to inhibit the growth of V. harveyi and the second result showed that the extract of G. verrucosa can increase the immune responses of shrimp. In the result of survival showed that shrimp fed with 0.5, 1.0, 1.5, and 2.0 g/kg has 80, 73, 70, and 70%, respectively. In conclusion, the seaweed extract of G. verrucosa has antibacterial activity and can induce the immune responses and resistance of Pacific white shrimp against V. harveyi infection. Keywords: Gracilaria verrucosa, seaweed, Vibrio harveyi, vibriosis,  Litopenaeus vannamei